Increase of bearing capacity concrete elements of building structures on compression - Shyshkina, O.O.; Shyshkin , O.O. (Ways to Improve Construction Efficiency, 2023)
The article describes the results of determining the influence of ultra-small doses of surface-active substances on the strength of artificial stone obtained from a mixture of nanopowders. the purpose of the work is to determine the effectiveness of the use of surface-active substances in ultra-small doses during the hardening of a mixture of cement nanopowder and calcium carbonate and gypsum nanopowder. The methodology of conducting experiments includes the following methods: analysis of studies on the use of nanopowders and surface-active substances; standard methods of testing building materials; comparative analysis; systematization and generalization of foreign and domestic experience. As a result of the research, the influence of surface-active substances applied in ultra-small doses on the strength of the artificial stone formed as a result of the hardening of nanopowder of calcium carbonate and cement was determined. It has been proven that in this case, the action of ultra-small doses of surface-active substances consists in reducing the number of open pores in the cement stone. Experimental studies have confirmed that molecules of surface-active substances, such as hyperplasticizers or others, significantly change the pH of the water used to make concrete. Increasing the mechanical strength of the obtained artificial stone allows replacing part of the cement nanopowder with a cheaper mineral nanopowder. It was established that an increase in the water-cement ratio in the mixture of nanopowders leads to an increase in the effectiveness of ultra-small doses of surface-active substances in the formation of compressive strength. The highlighted scientific materials became the starting point for understanding the researched issue. The effect of ultra-small doses of surface-active substances on the strength of artificial stone obtained from a mixture of nanopowders was identified and substantiated. The results of the research can be used in the production of concrete and reinforced concrete products and structures.